Diagnosis and management of Dermatophilosis in two cows and four buffaloes - Yalavarthi, Chaitanya; Deepti Balam; K.Suresh; Sai Soumya Konjeti (Indian Journal of Veterinary Medicine, 2024)
Two cows and four buffaloes were presented with the history of dermatitis of various degrees. Clinical examination revealed thick scabs all over the body with matting of hair. Skin scabs and scrapings were subjected to detailed cultural examination. Microscopical examination of Gram’s stained smears of scab material from the lesions revealed characteristic gram positive septate branching filaments with typical tram track appearance suggestive of Dermatophilus congolensis. Animals responded to oxytetracycline and tylosin combination and supportive therapy.